Combination of LOPCOW and MOORA in Restaurant Recommendation Decision Support System Based on User Reviews - Setiawansyah, Setiawansyah (Journal of Information Technology, Software Engineering and Computer Science (ITSECS), 2024)
A restaurant is a place of business that provides various types of food and beverages to be consumed on the spot or taken home. Restaurants are also often the venue of choice for various events, such as family gatherings, birthday celebrations, or business meetings. Restaurant recommendations based on user reviews are becoming an increasingly popular approach in helping individuals find the best places to eat according to their preferences. The purpose of the research is to develop an effective and objective decision support system in providing the best restaurant recommendations based on user reviews. This research makes a significant contribution to improving the quality of the user review-based recommendation system, by combining the advantages of objective data analysis (LOPCOW) and multi-criteria optimization (MOORA). The results of the combined ranking of the LOPCOW and MOORA methods show that Kedai Kita is ranked the highest with a score of 0.2897, followed by De'leuit Restaurant with a score of 0.284. Lemongrass Restaurant is in third place with a score of 0.2485, while Kluwih Sunda Authentic and Gurih 7 Bogor obtained a score of 0.2223 and 0.1981, respectively. The last position was occupied by RM Bumi Aki Puncak with the lowest score, which was 0.0396. These results show differences in performance or quality levels based on criteria analyzed using a combination of the two methods.